If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying z + -42 = -41 Reorder the terms: -42 + z = -41 Solving -42 + z = -41 Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '42' to each side of the equation. -42 + 42 + z = -41 + 42 Combine like terms: -42 + 42 = 0 0 + z = -41 + 42 z = -41 + 42 Combine like terms: -41 + 42 = 1 z = 1 Simplifying z = 1
| 20=5c-3 | | 2(x-3)=3x+3 | | x-0.6=9.36 | | 7e-9=19.7 | | ax=5a | | n^3-n=7n^2-5 | | n^3-n=7n^2-5 | | 3x=b/a | | 17(3)= | | 7p=50.4 | | 8x+14=12x-22 | | 3(x+5)+4(x-3)-6x=4 | | 17m=170 | | (x)(x+8)=96 | | 120-4x=40 | | 12-5x=-58 | | 7+9x=97 | | A(6a-3)= | | 2+8x=66 | | 6/2X+14 | | 11-4*x+1-3=11+2*4-2x-16 | | 7x-2=103 | | 3.5(c-8)+c=125 | | 6/(2X)=14 | | 9=6x-15 | | 2*4-2*3-x-1=4*2*4x-3+7-25 | | 6/2X=14 | | 4x-2=58 | | 9y^2+18y-3x+9=0 | | 2(s+6)+2(s-1)-4=74 | | 14-7x=-42 | | factorx^2-255x=100 |